Impact of clinical features on in-hospital outcomes in premature coronary artery disease patients post percutaneous coronary intervention - Noverike, Nikhen; Rohman, Mohammad Saifur; Rahimah, Anna Fuji; Rizal, Ardian; Prasetya, Indra (Universitas Brawijaya, 2024)
Background: Premature coronary artery disease (PCAD) is a significant health concern globally, characterized by the onset of coronary atherosclerosis at an early age. The development of PCAD is influenced by a variety of risk factors and leading to substantial morbidity and mortality. Despite advancements in interventions, the clinical and angiographic characteristics influencing in-hospital outcomes for these patients remain underexplored.Objective: This study aims to investigate the relationship between clinical features and in-hospital outcomes in patients with premature CAD post-percutaneous coronary intervention (PCI) at Dr. Saiful Anwar Hospital.Method: A retrospective cohort study was conducted on 1279 patients who underwent PCI for premature CAD from January 2022 to December 2023. Clinical data, including risk factors and angiographic findings, were collected from medical records. Statistical analyses were conducted using SPSS 22, employing univariate, bivariate, and multivariate logistic regression analyses to determine correlations.Result: The study included 1279 patients, with 438 in the premature CAD group and 841 in the non-premature CAD group. Significant differences were observed in age, sex distribution, BMI, lipid profiles, smoking status, and family history between the groups. Premature CAD patients were younger (mean age 50 vs. 64.8, p<0.001) and had higher rates of smoking and dyslipidemia. Angiographic analysis showed significant differences in LAD and LCx involvement and occlusion rates. In-hospital outcomes indicated higher incidences of shock, cardiac complications, and in-hospital mortality in the non-premature CAD group.Conclusion: Clinical and angiographic characteristics significantly influence in-hospital outcomes for premature CAD patients. Younger age, smoking, and dyslipidemia were prevalent risk factors. Enhanced management strategies focusing on these factors could improve patient outcomes.Keywords: Premature coronary artery disease, percutaneous coronary intervention, clinical characteristics, angiographic findings, in-hospital outcomes.Â